2015
DOI: 10.1111/1468-5922.12127
|View full text |Cite
|
Sign up to set email alerts
|

Winnicott's invitation to ‘further games of Jung‐analysis’

Abstract: Winnicott signs off his celebrated review of Jung's (1963) autobiography Memories, Dreams, Reflections with the warning that translation of 'erreichten' as 'attained' (implying assimilation) rather than as 'reached to', could 'queer the pitch for further games of Jung-analysis'. This subtly underscores his view that Jung--who he described earlier as 'mentally split' and lacking 'a self with which to know'--remained essentially dissociated. However, Winnicott, whilst immersed in this work on Jung, wrote a lette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In the wake of the review's completion he had, he reported to Michael Fordham, a dream, the content of which he explicitly associated to Jung: ‘I was also aware as the dream flowed over me before I quite became awake that I was dreaming a dream for Jung and for some of my patients, as well as for myself’ (Winnicott , p. 229). This dream has, in recent years, become in turn the subject of extensive commentary in the JAP – first by Morey (), then by Sedgwick () and more recently by Meredith‐Owen (, , ). I do not have the space here to review these fascinating commentaries.…”
Section: The Splitting Dreammentioning
confidence: 99%
See 3 more Smart Citations
“…In the wake of the review's completion he had, he reported to Michael Fordham, a dream, the content of which he explicitly associated to Jung: ‘I was also aware as the dream flowed over me before I quite became awake that I was dreaming a dream for Jung and for some of my patients, as well as for myself’ (Winnicott , p. 229). This dream has, in recent years, become in turn the subject of extensive commentary in the JAP – first by Morey (), then by Sedgwick () and more recently by Meredith‐Owen (, , ). I do not have the space here to review these fascinating commentaries.…”
Section: The Splitting Dreammentioning
confidence: 99%
“…In fact, as we have seen, Winnicott failed even to acknowledge Jung's claim that they represented an un‐pathological form of dissociation, in which the dynamic play and counterplay between two ‘personalities’ ultimately enabled the process of individuation – the movement toward the Self. Winnicott's doctrinaire theoretical commitment to the ‘unit‐self’ and the repression model, combined with an incapacity for a ‘fuller appreciation’ of Jung's psychology (Meredith‐Owen , p. 17), left no room for such dissociationist dynamics. His theoretical assumptions rendered them invisible to him.…”
Section: The Splitting Dreammentioning
confidence: 99%
See 2 more Smart Citations
“…But let us stay with Winnicott's contention that Jung's splitting off his unassimilated aggression and projecting it into enacted earthquakes or attributing it to God was at the cost of leaving him ‘dissociated’. I have previously discussed (Meredith‐Owen , , après Sedgwick ) the extent to which we might consider this version of Jung to be one coloured by Winnicott's need of a vehicle for addressing analogous issues in himself. But Saban would no doubt go much further and argue that this very same material could just as well be cited as an excellent example of psyche drawing on its inherent dissociability to constellate and manifest – through personification or enactment – a complex, so that growth might be facilitated through such an encounter.…”
mentioning
confidence: 99%